Reflecting on professionalism: an anlysis of Bachelor of Clinical Medical Practice (BCMP) students' portfolios during clinical rotations - Mapukata-Sondzaba, Nontsikelelo Olga (My University, 2014)
Globally there has been a reported increase in consumerism as a main driver of de-professionalization in the practice of medicine with a corresponding increase in cases of self-reported breaches of professionalism and ethical misconduct by students. This trend has necessitated a renewed focus on the experiences of professionalism among students in health care practice. Aim: The aim was to assess the Bachelor of Clinical Medical Practice (BCMP) students’ experiences and perceptions of professionalism during clinical rotations with a view to making recommendations designed to enhance congruency between the teaching and practice of professionalism as exhibited during clinical rotations. Methods: Following five-week attachments at purposefully selected clinical departments in designated District Education Campuses (DECs), final-year BCMP students were asked to reflect on Hatem’s definition of professionalism. Students reflected on their time in three of the five rotations, namely: Paediatrics (Paeds), Emergency Medicine (EM) and Adult in-Patient wards (AIPW). The research involved a collective case study of the three settings and took the form of a retrospective, descriptive, analytical and review-based design of 71 student portfolios. Qualitative methods were used to assess in the first instance the BCMP students’ ability to reflect critically and independently on moral and ethical issues (personal attributes). Secondly, quantitative elements were incorporated to evaluate the students’ ability to reflect on the core values of professionalism (contextual attributes) as determined by the Health Professions Council of South Africa. Results: With regards to personal attributes, the majority of BCMP students (n=54) reflected on the determinants of accountable and responsible practice. As they encountered a range of ethical issues/challenges, the most critical finding was the internalization of the Oath directly linked to students showing empathy to their patients. Many of the students (n=51) were motivated to exhibit model behaviour, and recognised the value of constant reflection as a skill. Just over a third of the students (n=25) reflected on feeling like “guinea pigs” going through a period of uncertainty to becoming “teachable learners” who accepted the responsibility of becoming future role models as members of their profession. Because of the shortage of health care workers and an increasing burden of disease, the BCMP students felt pressured into “pushing the line”. Professionalism with regard to contextual attributes was presented as positive experiences (53.8%) with the BCMP students developing a good work ethic as they were mentored, observed role modelling and functioned as part of a team. Comparatively, negative experiences of professionalism (46.2%) were context-specific as students had to navigate parents’ or family interests; as well as traditional and cultural practices. The unprofessional behaviour of a few individuals resulted in access to health care being compromised, inadequate or in extreme cases denied, with student learning compromised. Conclusions: Portfolios provided a medium through which the voices of the BCMP students could be heard. The internalization of the Oath could possibly be attributed to an integrated curriculum and early exposure to the clinical training environment. Students were drawn to health care workers who embodied a good work ethic and expressed a desire to emulate such behaviours. The role of clinical teachers is critical in graduating a morally competent, ethically reflective and professional health care worker.
Keywords: Medicine; Professional Practice